2023
DOI: 10.1039/d3gc00104k
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the biosynthesis of bio-based PET and PEF polyester monomers

Abstract: With the rapid development of modern industry and increasing scarcity of petroleum resources, bio-based polymeric materials using biomass resources as the primary raw material, with dual roles in resource conservation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 129 publications
0
14
0
Order By: Relevance
“…In recent years, the preparation, modification, and implementation of polyesters based on 2,5-furandicarboxylate (2,5-FDCA) have attracted much attention. ,,, Poly­(ethylene 2,5-furandicarboxylate) (PEF) has attracted much attention owing to its green production methods, high glass transition temperature ( T g ), excellent mechanical properties, superior barrier features, and so on. , We studied the literature and observed that most of the scientific reports provided good ideas for the next generation of packaging components, which will be considered to have the potential to replace polyethylene terephthalate (PET). , The modulus of elasticity of PEF is a little higher than that of PET . In addition, the barrier performance of PEF is better than that of PET owing to the limited conformational movement due to the more rigid furanoate groups .…”
Section: Most Important 25-fdca-based Homopolyestersmentioning
confidence: 99%
“…In recent years, the preparation, modification, and implementation of polyesters based on 2,5-furandicarboxylate (2,5-FDCA) have attracted much attention. ,,, Poly­(ethylene 2,5-furandicarboxylate) (PEF) has attracted much attention owing to its green production methods, high glass transition temperature ( T g ), excellent mechanical properties, superior barrier features, and so on. , We studied the literature and observed that most of the scientific reports provided good ideas for the next generation of packaging components, which will be considered to have the potential to replace polyethylene terephthalate (PET). , The modulus of elasticity of PEF is a little higher than that of PET . In addition, the barrier performance of PEF is better than that of PET owing to the limited conformational movement due to the more rigid furanoate groups .…”
Section: Most Important 25-fdca-based Homopolyestersmentioning
confidence: 99%
“…Some consumer plastics, currently produced from petroleum or natural gas, are being produced from various biomass feedstocks. For example, producing biomass-derived terephthalic acid, a monomer precursor for polyethylene terephthalate (PET) and polybutylene adipate terephthalate (PBAT), has been attracting much research effort, but industrial scale processes are rare. Companies such as Anellotech and Suntory have been able to produce PET from wood. , Braskem commercially produces high-density polyethylene (HDPE) from bioethanol. , Biobased versions of PET, polypropylene (PP), and HDPE have the same properties as PET, PP, and HDPE produced from petroleum and are not biodegradable. Also, many polyamides on the market are (partly) biobased.…”
Section: Definitions Of Biodegradable Plastics and Plastic Biodegrada...mentioning
confidence: 99%
“…25–29 In addition to these methods that require prefunctionalization of aromatic substrates, aromatic carboxylic acids can also be prepared via direct carboxylation of aromatic compounds with CO 2 , such as base-mediated carboxylation, 30,31 Lewis acid-mediated carboxylation, 32,33 transition metal-catalyzed carboxylation, 34–38 and enzymatic carboxylation. 39,40 However, these methods suffer from drawbacks such as the need to use stoichiometric metallic reductants or harsh conditions. 25–40 Carboxylation with CO 2 using electrocatalysis is a promising alternative for synthesizing aryl carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 However, these methods suffer from drawbacks such as the need to use stoichiometric metallic reductants or harsh conditions. 25–40 Carboxylation with CO 2 using electrocatalysis is a promising alternative for synthesizing aryl carboxylic acids. However, its application is impeded by sacrificial anodes and insufficient selectivities.…”
Section: Introductionmentioning
confidence: 99%